Design, Formulation and Evaluation of Fast Disintegrating Tablets of Glipizide - Brahma, Dillip Kumar; Sharma, Neeraj (Journal of Drug Delivery and Therapeutics, 2019)
Diabetes mellitus is metabolic disorder it is caused by an absolute or relative lack of insulin that, among other consequences, to increase in plasma glucose concentration associated with change hyperglycemia and disturbance of lipid metabolism, carbohydrate metabolism, also protein metabolism. Absolute lack of insulin called as Type 1 diabetes mellitus also called as juvenile diabetes. The condition caused by a lesion in the beta cells of the pancreas. Type 2 diabetes is a long term metabolic disorder that characterized by high blood sugar , insulin resistance ,and relative lack of insulin/ The prepared tablets were adequately hard to withstand pressure the hardness ranged from (2.91-3.67). The friability from the tablets was less which represent less loss of free particles. The weight variation and wetting were within limits. The dissolution of prepared tablets was relatively fast. Keywords: Diabetes mellitus, glipizide, Fast Disintegrating Tablets.